Improving Student’s Creative Thinking Skills using the Case Based Learning (CBL) Model assisted by Virtual Laboratory Media on Optical Materials - Muhyi, Abdul; Windrawan, I Gede; Astra, I Made (Jurnal Penelitian Pembelajaran Fisika, 2024)
Abstract. The research aimed to assess the improvement of students' creative thinking skills through the implementation of the Case Based Learning (CBL) model, supported by a Virtual Laboratory, in the topic of Optics. The method used was Classroom Action Research (CAR) involving 41 students from class XI MIPA 6 at SMA Negeri 6, Kabupaten Tangerang. The research was designed in three cycles, each consisting of four stages: planning, action, observation, and reflection. The results indicated that the application of the CBL model, assisted by the Virtual Laboratory, significantly enhanced students' creative thinking abilities. The average percentage of students categorized as "Highly Creative" increased from 12.1% in the first cycle, to 29.2% in the second cycle, and reached 58.04% in the third cycle. Meanwhile, the percentage of students in the "Not Creative" category decreased from 24.3% in the first cycle, to 9.7% in the second cycle, and dropped to 0% in the third cycle. These findings suggest that integrating the CBL model with a virtual laboratory is not only effective in boosting creative thinking skills but also in deepening students' understanding of physics concepts visually. The implications of this research indicate that the use of Virtual Laboratory within the CBL model provides a strong framework for innovative teaching practices in physics education, which can enhance the effectiveness of learning and student motivation.